Financial Literacy at Work: Enhancing Organizational Performance through Employee Training Investments - Lestari, Setyani Dwi; Muhdaliha, Eryco; Firdaus, Pantja Maulana; Suhendra, Euphrasia Susy; Brabo, Nora Andira (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study investigates the impact of financial literacy programs on organizational performance, focusing on how such training influences employee financial behavior, workplace satisfaction, and productivity. Employing a qualitative research methodology, the study utilizes in-depth interviews, focus groups, and document analysis to explore the subjective experiences and perspectives of employees participating in financial literacy initiatives. The results reveal that financial literacy programs significantly enhance employees' financial behaviors, including improved budgeting, saving, and debt management. These improvements lead to increased financial security and reduced stress, contributing to higher workplace satisfaction and engagement. Furthermore, the study finds that financial literacy positively affects organizational performance by reducing absenteeism, lowering turnover rates, and enhancing productivity. Employees with better financial literacy are more likely to participate in employer-sponsored benefits and report greater job satisfaction. The integration of financial literacy into broader employee wellness strategies is shown to be particularly effective, fostering a more holistic approach to employee well-being. Technological advancements, such as digital tools and online platforms, enhance the accessibility and effectiveness of financial literacy programs, making them more engaging and adaptable to various learning preferences. The study concludes that investing in tailored, ongoing financial education is crucial for organizations seeking to improve employee well-being and achieve long-term business success. Future research should continue to explore the long-term effects of financial literacy programs and the role of technology in providing effective financial education.